Urinary diversion after radical cystectomy for bladder cancer: options, patient selection, and outcomes. (January 2014) - Lee, Richard K.; Abol‐Enein, Hassan; Artibani, Walter; Bochner, Bernard; Dalbagni, Guido; Daneshmand, Siamak; Fradet, Yves; Hautmann, Richard E.; Lee, Cheryl T.; Lerner, Seth P.; Pycha, Armin; Sievert, Karl‐Dietrich; et al.
Abstract : Context: The urinary reconstructive options available after radical cystectomy (RC) for bladder cancer are discussed, as are the criteria for selection of the most appropriate diversion, and the outcomes and complications associated with different diversion options. Objective: To critically review the peer‐reviewed literature on the function and oncological outcomes, complications, and factors influencing choice of procedure with urinary diversion after RC for bladder carcinoma. Evidence Acquisition: A Medline search was conducted to identify original articles, review articles, and editorials on urinary diversion in patients treated with RC. Searches were limited to the English language. Keywords included: 'bladder cancer', 'cystectomy', 'diversion', 'neobladder', and 'conduit'. The articles with the highest level of evidence were selected and reviewed, with the consensus of all of the authors of this paper. Evidence Synthesis: Both continent and incontinent diversions are available for urinary reconstruction after RC. In appropriately selected patients, an orthotopic neobladder permits the elimination of an external stoma and preservation of body image without compromising cancer control. However, the patient must be fully educated and committed to the labour‐intensive rehabilitation process. He must also be able to perform self‐catheterisation if necessary. When involvement of the urinary outflow tract by tumour prevents the use of an orthotopic neobladder, a continent cutaneous reservoir may still offer the opportunity for continence albeit one that requires obligate self‐catheterisation. For patients who are not candidates for continent diversion, the ileal loop remains an acceptable and reliable option. Conclusions: Both continent and incontinent diversions are available for urinary reconstruction after RC. Orthotopic neobladders optimally preserve body image, while continent cutaneous diversions represent a reasonable alternative. Ileal conduits represent the fastest, easiest, least complication‐prone, and most commonly performed urinary diversion.